Firm heterogeneity: Do destinations of exports and origins of imports matter? - Francesco Serti; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
How do importing activities matter in explaining firm heterogeneity? How firm performances are related to foreign markets heterogeneity? Using a rich database on Italian manufacturing firms, this essay adds new evidence on the relationship between trade status and firm characteristics. We uncover evidence supporting recent theories on firm heterogeneity and international trade, together with some new facts. First, the availability of information on import and export enables us to differentiate firms involved in both trading activities - namely two-way traders - from firms that only export, and from those that only import. We show that firms engaged in both import and export outperform those involved in either importing or exporting only. Second, exploiting firm-level information on the destination of export and the origin of imports, we observe the heterogeneity among firms trading with different type of markets. We show that different destinations of exports and different origins of imports map into distinctive firm characteristics.
Keywords: F10; F16; J21; 330; heterogeneous firms; exports; imports; productivity; performances; destinations; Export; Import; Unternehmenserfolg; Produktivität; Internationaler Markt; Diversifikation; Italien